PERILLUS BIOCULATUS (FABRICIUS) (HETEROPTERA: PENTATOMIDAE) IN SERBIA (Acta Entomologica Serbica, 2012)
In 1996, in order to study flora and vegetation the members of the science-expert expedition to the Prokletije Mt. - locality named Djeravica, collected  specimens of Perillus bioculatus (Fabricius, 1775), a new species for the fauna of Serbia. This is the third point in the distribution of P. bioculatus (F.) in the Balkan Peninsula: Bulgaria (Stara Planina Mt., Maleshevska Planina Mt.), Greece (Larissa), Serbia (Prokletije, Mt.).